A New Enhanced Sorbitol: Calcium Diphosphate Composite as A Direct Compression Excipient: A Comparative Study (2016)
ABSTRACT: Objective: To evaluate and compare the particle and tableting properties of a new sorbitol (SOR) and anhydrous calcium diphosphate (ACD)composite with common excipients used for the preparation of tablets by direct compression such as polyvinylpyrrolidone (Ludipress®), lactose (Cellactose 80®) and microcrystalline cellulose (Prosolv SMCC 90®). Methods: All materials were tested for lubricant sensitivity, ejection force, and elastic recovery, dilution potential and reworking ability. Further, compressibility and compactibility were determined using the Heckel and Leuenberger models, respectively.Results: This new excipient offered more benefits in terms of functionality than commercial direct compressive co-processed excipients andshowed better compressibility than other commercial excipients and its compactibility was ranked third after SOR and Prosolv SMCC 90®. However, this composite material was more susceptible to reprocessing than commercial products. Further, it showed a low lubricant sensitivity due to a combination of a plastic and brittle behavior. Moreover, the loading capacity of poorly compressible materials such as gemfibrozil was comparable to that of commercial direct compression excipients. It also showed the fastest in-vitro dissolution of gemfibrozil, whereas commercial products failed to fulfill the US pharmacopoeial requirements. Conclusion: This new composite material showed potential for use as a direct compression excipient.